2007
DOI: 10.1080/14622200601080315
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming barriers to recruitment and retention in adolescent smoking cessation

Abstract: Participant recruitment and retention have been identified as challenging aspects of adolescent smoking cessation interventions. Problems associated with low recruitment and retention include identifying smokers, obtaining active parental consent, protecting participants' privacy, respecting participants' autonomy, and making participation relevant and accessible to adolescents. This paper describes nine strategies for minimizing these recruitment and retention problems via a proactive telephone counseling int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 0 publications
3
20
0
Order By: Relevance
“…Working with minors, researchers found that success in clinical research required a mix of trust, confidentiality, and continuous contact with young patients and their guardians [18,21,24,26,30,32,37,38]. Earning confidence often included earning the trust of the communities from which patients were recruited.…”
Section: Resultsmentioning
confidence: 99%
“…Working with minors, researchers found that success in clinical research required a mix of trust, confidentiality, and continuous contact with young patients and their guardians [18,21,24,26,30,32,37,38]. Earning confidence often included earning the trust of the communities from which patients were recruited.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, including nonsmokers provides the intervention an opportunity to harness nonsmokers' support in helping their smoking friends to quit and, more important, an opportunity to evaluate the effectiveness of their doing so. Finally, as it turned out, including nonsmokers may have boosted recruitment of smokers to the intervention (Kealey et al, 2007).…”
Section: Experimental Designmentioning
confidence: 99%
“…The smoking cessation intervention incorporates multiple strategies to address known intervention obstacles (Kealey et al, 2007), including (1) proactively identify smokers in the population and directly invite their participation; (2) include both smokers and nonsmokers as participants to protect smokers' privacy; (3) use the telephone to proactively deliver the intervention; (4) allow unlimited calls to reach adolescents; (5) tailor the intervention to the individual; and (6) communicate respect for adolescents and their choices.…”
Section: Intervention Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, although participants were more likely to attend if they had more positive perceptions of smoking, higher baseline smoking rate, higher baseline nicotine dependence, and were of white race, attendance was not associated with baseline motivation to quit, perceived stress, previous quit attempts, gender, or age. In another study, 72% of participants completed the multiple-session telephone counseling intervention, with lower baseline smoking frequency and later stage of change to quit being associated with higher treatment completion rates [10].…”
mentioning
confidence: 98%